Cultural Phenomenon is the measure problem of Ethnic Students in learning mathematics - Pokharel, Jagat Krishna (Innovative Research Journal, 2022)
The aim of the study was to identify the measure language difficulties in mathematics of the students in basic level class room and relation between language and learning mathematics. The finding of the study indicates that the student’s language difficulties in two categories the first one are sematic difficulties. These difficulties include that the student suffering mathematics due to specific terms. The terms having different meaning in other Description in the theorem properties and the use of notation. Another difficulty are synthetic difficulties; this difficulty is use of language; mathematics need to be explained with the help of language. Every language has its specific formal structure and pattern which is called the synthetic language. The study has a hypothesis that the ethnic students have great discontinuity between their everyday life and school activities as the get practical Knowledge in home and theoretical knowledge at school. This study tries to find out the problem faced by the ethnic student in learning mathematics to be making co-operative class environment and to be serious thought while making decision about curriculum and teaching learning process.